COMPARISON OF EPITHELIAL CELL COUNTS BETWEEN MIDDLE AND LATERAL LOBES IN BENIGN PROSTATIC HYPERPLASIA (BPH) PATIENT - Rahman, Eka Yudha; Singodimedjo, Prawito (Indonesian Journal of Urology, 2010)
Objective: The aim of this study was to compare the epithelial cell counts in each lobe of prostate glands with benign prostatic hyperplasia (BPH). Material and methods: Twenty-two BPH patients who underwent transurethral resection of the prostate (TURP) in Diponegoro Dua Satu Surgery Hospital Klaten, from May until November 2006 were enrolled in this study. Tissue from each lobe of the prostate gland was separately collected, from the middle (A), left lateral (B), right lateral lobes (C). All samples were fixed in 10% formalin buffer, embedded in paraffin and sectioned in 4 micrometer slices with microtome. After hematoxylin eosin (HE) staining, number of epithelial cells was counted under light microscopy. Difference in epithelial cell counts in each alveolus between the three lobes was statistically analyzed using t-test (p<0,05). Results: Twenty-two patients were included in this study from May to November 2006, mean age was 66,64±7,6 (54-88) years old. The most common occupation was farmer. Almost all patients had symptoms of chronic urinary retention (95,45%). Length of hospital stay was 8,77±2,7 (6-17) days, mean weight of prostate resected was 47,05±23,2 (5-90) grams, mean operative time 77,73±22,24 (45-115) minute, mean volume of irrigation fluid (sterile water) was 24,18±7,87 (5-34) liter. Mean number of cells in groups A, B, and C were 23,67±8,4 (13,6-44,4), 29,22±8,8 (16,4-41,2), and 29,11±8,7 (16,4-41,2) respectively. There was significant difference between groups A and B, and between groups A and C (p<0,05) respectively. Conclusion: There was statistically significant difference in epithelial cell count between the middle lobes compared to lateral lobes of the prostate in BPH surgical samples. These findings are supported by cystoscopic observation of smaller middle lobe compared to the lateral lobes in BPH.